A study on Christian librarians in the Philippines and the integration of their faith in the profession - Enriquez, Kevin Vincent M.; Pascua, Sonia M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Christian librarians are distinguishing themselves in foreign countries. They argue that they practice librarianship in a unique way. They have established large organizations such as the Association of Christian Librarianship (ACL) and the Fellowship of Christian Librarians and Information Scientists (FOCLIS) and have published numerous articles for the development of Christian librarianship. While a formal definition of Christian librarianship has yet to be formulated, close inspection of literature shows that the core characteristics of Christian librarianship is having faith in Jesus Christ and integrating that faith in librarianship. In the Philippines, information resources and even common knowledge of Christian librarianship is very scarce, leading to the question of whether it exists in the Philippines. It is in this light that this study aimed to investigate the existence of Christian librarianship in the Philippines and the extent of its practice.
A total of 24 librarians who self-identifies as Christian of any denomination were invited to participate in focus group discussions. The Worldview index was used to determine if the librarians adopt a Christian worldview. Their opinions, views, and ideas where then sought out to determine the presence of their Christian worldview in selected areas of librarianship, and to gather their first-hand experience in integrating faith in librarianship.
Analysis of the discussions revealed that there are librarians whose primary motivation to pursue excellence in librarianship is to please God and leading others to Christ through their actions. The Christian worldview is manifested in the decision-making process, attitude towards work and relationships with people, and views on censorship. However, the role of Christian worldview in the technical aspects of librarianship is minimal. The interaction between the technical aspects of both Christianity and librarianship is minimal as well as seen in the minimal role of librarianship in the librarian's ministry. Lastly, the librarians recognize the difference in practice their Christian worldview caused in their work. However, they find it difficult to distinguish themselves as Christian librarians due to the lack of formal standards and concrete practices.
Despite the lack of knowledge of people on the concept, the practice of Christian librarianship in the Philippines exists. The practice of Christian librarianship is mostly seen inwards--towards the attitude, dedication, motivation, decision-making and relations of the librarian. On the other hand, the role of Christian worldview on the technical aspects of librarianship is minimal other than the effects of ethics, dedication and attitudes have.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- Religious aspects; Christian librarians